Xenobiotics, Trace Metals and Genetics in the Pathogenesis of Tauopathies - Jan Aaseth (International Journal of Environmental Research and Public Health, 2020)
Tauopathies are a disease group characterized by either pathological accumulation or release of fragments of hyperphosphorylated tau proteins originating from the central nervous system. The tau hypotheses of Parkinson’s and Alzheimer’s diseases contain a clinically diverse spectrum of tauopathies. Studies of case records of various tauopathies may reveal clinical phenotype characteristics of the disease. In addition, improved understanding of different tauopathies would disclose environmental factors, such as xenobiotics and trace metals, that can precipitate or modify the progression of the disorder. Important for diagnostics and monitoring of these disorders is a further development of adequate biomarkers, including refined neuroimaging, or proteomics. Our goal is to provide an in-depth review of the current literature regarding the pathophysiological roles of tau proteins and the pathogenic factors leading to various tauopathies, with the perspective of future advances in potential therapeutic strategies.